2010
DOI: 10.1007/s10464-010-9401-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adulthood and Leaving Foster Care: Settings Associated with Mental Health

Abstract: The present study examined the role of contextual support on mental health during the transition to adulthood within a vulnerable group, adolescents leaving foster care because of their age. Participants were 265 19- to 23-year-olds who retrospectively reported on 3 main contexts of emerging adulthood: housing security, educational achievement, and employment attainment in the first 2 years after leaving foster care. Mental health measured self-reported emotional distress, substance abuse, and deviancy at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 53 publications
6
45
0
Order By: Relevance
“…Such findings are reflected in studies that have attempted to capture the heterogeneity of care leavers' experiences by describing various types or classes of care leavers. Despite the differences across these studies, each identified a particular subgroup of care leavers with the most disrupted care experiences, the highest prevalence of mental health conditions, significant social isolation and the worst post-care outcomes (Fowler et al, 2011;Keller et al, 2007;Stein, 2006). …”
Section: Leaving Care and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings are reflected in studies that have attempted to capture the heterogeneity of care leavers' experiences by describing various types or classes of care leavers. Despite the differences across these studies, each identified a particular subgroup of care leavers with the most disrupted care experiences, the highest prevalence of mental health conditions, significant social isolation and the worst post-care outcomes (Fowler et al, 2011;Keller et al, 2007;Stein, 2006). …”
Section: Leaving Care and Mental Healthmentioning
confidence: 99%
“…Children and young people who have been placed in care for behavioural reasons (e.g., delinquency or substance abuse) have been found to have poorer mental health outcomes than those placed due to abuse and neglect (Vinnerljung & Sallnäs, 2008); however, this does not preclude the possibility that such young people have also experienced adverse childhood events. Additionally, children and young people who experience lower placement stability (Barth et al, 2007;Fechter-Leggett & O'Brien, 2010;Ford et al, 2007;Fowler, Toro, & Miles, 2011), those who experience residential care placements (Akister et al, 2010;McMillen et al, 2005;Tarren-Sweeney, 2008a) and young people exposed to maltreatment in care (FechterLeggett & O'Brien, 2010) are also more likely to experience mental health issues. It is important to note that these are not necessarily causative factors, rather that they are likely to be inter-related and reinforcing in relation to their impact on mental health.…”
Section: Mental Health Of Out-of-home Care Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Transition difficulties for youth aging out of foster care are further exacerbated by limited financial resources and few personal and family connections. 9 The available evidence indicates multiple challenges to mental health care transitions among youth aging out of foster care, and suggests the importance of transition planning, continuous insurance coverage, and community supports for education, employment, and housing. 10 Effective since January 2014, the Affordable Care Act (ACA) includes a provision that all youth in foster care, on or after their 18th birthday, are eligible for Medicaid until 26 years old.…”
Section: What's Newmentioning
confidence: 99%
“…Identified themes underscore that mental health care transitions for youth aging out of foster care must be addressed in concert with other key transition needs, including education supports, employment skills, and housing stability. 5,9,10 As youth struggle to grapple with transitions and loss of previous support systems, findings indicate that personal psychosocial supports and formal community-based transitional supports are necessary to promote mental health and overall well-being. 13,32 Providing youth with clear information on Medicaid eligibility and enrollment is essential.…”
Section: Practice and Policy Implicationsmentioning
confidence: 99%